Mentoring of Pregnant Women at High Risk Program (Gerdaristi) to Reduce Maternal and Infant Mortality in Nganjuk, East Java - Ratnaningsih, Titin; Joebagio, Hermanu; Murti, Bhisma (Journal of Maternal and Child Health, 2016)
Background: Maternal and infant mortality has the third rank in East Java. The effort to reduce the number of maternal and infant mortality is through Mentoring Program Pregnancy and High Risk Infants Mortality or Gerakan Pendampingan Ibu Hamil Beresiko Tinggi (Gerdaristi). This study aimed to investigate the success rate of implementation of Gerdaristi program in reducing Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) in Nganjuk. Subjects and Method: This was a case study with qualitative method. This was conducted in Nganjuk, East Java.